2020
DOI: 10.1186/s12883-020-1615-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between non-high-density lipoprotein cholesterol and haemorrhagic transformation in patients with acute ischaemic stroke

Abstract: Background It is unclear whether non-high-density lipoprotein cholesterol (Non-HDL-C) is associated with haemorrhagic transformation (HT) after acute ischaemic stroke (AIS). We aimed to explore the association between Non-HDL-C and HT, as well as compare the predictive values of Non-HDL-C and low-density lipoprotein cholesterol (LDL-C) for HT. Methods We consecutively enrolled AIS patients within 7 days of stroke onset. Participants were divided in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
(44 reference statements)
1
13
0
Order By: Relevance
“….83], respectively, P for trend = 0.024). [21] With the current studies, the associations between LDL and the incidence of ICH was warrant to be tested. There were many limitations within the current study.…”
Section: Discussionmentioning
confidence: 96%
“….83], respectively, P for trend = 0.024). [21] With the current studies, the associations between LDL and the incidence of ICH was warrant to be tested. There were many limitations within the current study.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, a lower LDL/HDL ratio was linked to worse outcomes at three months (including death, recurrence, and moderate disability) after stroke [ 29 ]. In another study, low levels of non-HDL cholesterol and LDL were associated with an increased risk of hemorrhagic transformation after ischemic stroke [ 30 ]. However, these studies, including our study, demonstrate associations, not causative relationships, and the mechanisms underlying these associations are still to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that atherosclerosis (AS) is the most common cause of AIS, and dyslipidemia is the most important risk factor of AS (3,4). Many blood lipid parameters have been used to evaluate the risk of stroke outcomes, such as total cholesterol (TC), triglyceride (TG), lowdensity lipoprotein (LDL-C), high-density lipoprotein (HDL-C), non-HDL-C, and other parameters (5)(6)(7)(8), but the predictive values of these indicators are still limited.…”
Section: Introductionmentioning
confidence: 99%